Increased temperature induces leaffolder outbreak in rice field. (29th May 2019) - Ali, Md. Panna; Kabir, Mir Md. Moniruzzaman; Afrin, Sadira; Nowrin, Farzana; Haque, Sheikh Shamiul; Haque, Md. Maksudul; Hashem, Abeer; Tabassum, Baby; Abd_Allah, Elsayed Fathi; Pittendrigh, Barry Robert
Abstract: The rice leaffolder, Cnaphalocrosis medinalis Güenée (Lepidoptera: Crambidae), has emerged as a serious pest with significant outbreaks over the last decade in several rice‐growing countries, including China and Bangladesh and resulting in heavy rice yield losses. Climate changes (particularly high temperatures in late winter in Bangladesh) coincide with upsurge in outbreaks of this pest. We generated a statistical model using more than two decades of data to show that increased temperatures associate with this upsurge. Over the 22‐year model period, leaffolder populations in November increased significantly, corresponding to significant monthly temperature trends (but not rainfall) over the same period. Utilizing a linear model, we find that increasing temperature interacts with the amount of rainfall. With the variable month as a proxy for all seasonal effects affecting leaffolder abundance, the model reveals a significant correspondence with climate variations compared to average conditions; specifically, the model predicts that increasing maximum temperatures will lead to more leaffolder, while more rain will decrease their abundance. This study suggests that warmer environment contributed to recent outbreaks of leaffolder in rice‐growing countries; thus, climate change increases rice yield losses by increasing pest population in the field.